Feeding adequacy among critically ill patients in the Intensive Care Unit and its association with clinical outcomes: a narrative review - Lee, Zheng Yii; Mohd Yusof, Barakatun Nisak; Ibrahim, Noor Airini (Bangladesh Society of Critical Care Medicine, 2017)
The Intensive Care Unit (ICU) is one of the disciplines in the hospital that provides close monitoring to the seriously ill or injured patients, also known as the critically ill patients. Critically ill patients in the ICU are usually unable to maintain volitional oral nutrition intake and therefore require nutritional therapy. Nutritional therapy can be delivered via the enteral or parenteral route. Optimal nutrition adequacy (i.e. neither underfeeding nor overfeeding) is very important for better clinical outcome. However, the problem of suboptimal feeding adequacy continues to be reported over the years. This article attempts to give an overview of the literature on feeding adequacy and the relationship of feeding adequacy with clinical outcomes among the critically ill patients in the ICU.